Design on switching sequence for control circuit by using Altera Max+Plus II - Aziz, Roziah (2007)
The purpose of this research work is to design digital switching sequence for control circuit. A digital system comes with more benefit than analog which is programmable, faster, precise and flexible. These proposed digital switching sequences are application for single-phase and three-phase inverters. By controlling analog circuits digitally, system cost and power consumption can be drastically reduced. The switching sequences are designed using Altera Max+Plus II and downloaded to University Program (UP1) development board unit which consists of two types of Complex Programming Logic Devices (CPLD). In this research work, MAX7000 has been chosen to download the proposed switching sequence that has been designed. To prove the validity of the switching sequences chosen for single-phase and three-phase inverter, MATLAB/ Simulink is used as the simulation software. At the end of this research work, the digital switching sequences for single-phase and three-phase inverter have successfully been designed.